Genealogie nachmetaphysischen Denkens: Zur Philosophiegeschichte von Jürgen Habermas - Wenz, Gunther (Kerygma und Dogma, 2020)
In his recently published history of philosophy, Jürgen Habermas offers a genealogy of postmetaphysical thinking focused on the problem of faith and knowledge as well as a reconstruction of the genesis of his own theory of communicative action. This review analyses, among other things, Habermas’s understanding of metaphysics and theology that stand behind his talk of postmetaphysical thought.